IMPLEMENTASI ANALISIS STP (SEGMENTATION, TARGETING, POSITIONING) PADA USAHA KUE TRADISIONAL DJAJE - Sephy Lavianto; I Made Artana; Made Irvan Mahendra Putra (Politeknik Bisnis Indonesia, 2022)
Djaje is a traditional cake business that was founded in 2017. The products that Djaje sells are various wet snacks. The initial strategy used was only offline, such as handing cakes to resellers, but as the number of competitors increased, Djaje's sales declined. This research uses method analysis STP (Segmentation, Targeting, Positioning) the data is then presented with a qualitative descriptive method. The purpose of this study was to determine the results of implementing digital marketing strategies in improving traditional cakes. The results of the implementation of the strategy implemented by adjusting the content of photos, descriptions, posts, and advertisements using STP (Segmentation, Targeting, Positioning) analysis as a basis. By utilizing various digital platforms to reach more potential consumers, Djaje managed to make cake sales increase from October 2021 by Rp. 10,000,000 per month until March 2022 reaching Rp. 25,092,500 with total sales for 6 months of Rp. 105,832,500.